Alcohol use in adolescence: a qualitative longitudinal study of mediators for drinking and non-drinking. (2nd November 2022) - Buvik, Kristin; Tokle, Rikke; Bilgrei, Ola Røed; Scheffels, Janne
Abstract: Initiation of alcohol use often takes place in adolescence. This longitudinal study explores adolescents' alcohol use by highlighting mediators in their network that either hinder or facilitate alcohol consumption. Qualitative individual interviews were conducted with 75 adolescents (age 15–16) during their final year of lower secondary school (LSS), and their first year of upper secondary school (USS) (age 16–17), amounting to 150 interviews in total. Three drinking practices were identified during the transition from LSS to USS. The abstainers did not drink either in LSS or USS. They emphasized negative effects of alcohol and ascribed their non-drinking to the mediating role of parental expectations, sports and school achievements, and weak social ties. The initiators started to drink in USS and described increased acceptance, availability, peer pressure and social benefits as mediators for alcohol use initiation. The drinkers drank alcohol in both LSS and USS, and the mediators for drinking ranged from curiosity and social lifestyles to personal vulnerability traits. This study identified hindering and facilitating mediators for drinking, but also highlighted blurred boundaries between drinking and non-drinking: non-drinkers recognized social benefits associated with drinking, and drinkers highlighted control and responsible drinking alongside the pleasure and social benefits of drinking.